Birds Must Be Eliminated: Air Architecture and the Planetary Reenactment of the Modern Void. Issue 2 (2nd July 2016) - Salgueiro Barrio, Roi
Abstract : This article analyzes Air Architecture, a work the artist Yves Klein developed with the help of architects Werner Ruhnau and Claude Parent, with the aim of situating it as an alternative intervention in the urban debates of the late 1950s. It reads Air Architecture in relation to the procedures that Klein used in his artistic work to understand how the project accomplishes two main goals: first, to highlight the strategic value that emptiness and the resulting void spaces had for urban modernism, and second, to critically examine the validity of that strategy in facing the emergence of a global urban society and the social transformation from industrialism to consumerism during the 1950s.